Pembatalan Akta Perjanjian Pengikatan Jual Beli Hak Atas Tanah Oleh Pengadilan Akibat Wanprestasi (Deposisi: Jurnal Publikasi Ilmu Hukum, 2025)
Land purchase transactions in Indonesia, which often involve customary practices and are governed by law, require a written agreement, such as a Sale and Purchase Agreement (PPJB), to prevent conflicts. The PPJB binds both parties and is subject to civil law. In case of a breach of contract, the agreement may be canceled through the court. A breach of contract accompanied by fraud can result in criminal liability, and the affected party may file a civil lawsuit to annul the transaction. This study aims to (1) examine the legal consequences for the parties following the cancellation of a sale and purchase agreement for land rights by the court due to breach of contract; and (2) explore the legal protection available in the cancellation of such agreements in Indonesia. The research method employs a normative legal approach with a literature review, analyzing relevant laws, theories, and court decisions through primary and secondary legal materials. The analysis is qualitative, linking court decisions to the issues addressed in the study. The findings indicate that, in contract law, particularly in land sales, certain principles and conditions govern the validity of agreements. In the event of a breach of contract, the injured party may seek to annul the agreement in court if subjective (agreement, capacity) or objective (valid object and cause) requirements are not met. Cancellation of the agreement restores the parties to their original positions, allowing for the return of any goods exchanged. A breach of contract, where one party fails to fulfill its obligations, may lead to cancellation and compensation. Contract law provides legal protection to the injured party, including the right to demand performance, annulment, and compensation as outlined in the Civil Code.